The Trifecta of Tele-Critical Care: Intrahospital, Operational, and Mass Casualty Applications. (25th January 2021) - Ieronimakis, Kristina M; Colombo, Christopher J; Valovich, Justin; Griffith, Mark; Davis, Konrad L; Pamplin, Jeremy C
ABSTRACT: Introduction: Tele-critical care (TCC) has improved outcomes in civilian hospitals and military treatment facilities (MTFs). Tele-critical care has the potential to concurrently support MTFs and operational environments and could increase capacity and capability during mass casualty events. TCC services distributed across multiple hub sites may flexibly adapt to rapid changes in patient volume and complexity to fully optimize resources. Given the highly variable census in MTF intensive care units (ICU), the proposed TCC solution offers system resiliency and redundancy for garrison, operational, and mass casualty needs, while also maximizing return on investment for the Defense Health Agency. Materials and Methods: The investigators piloted simultaneous TCC support to the MTF during three field exercises: (1) TCC concurrently monitored the ICU during a remote mass casualty exercise: the TCC physician monitored a high-risk ICU patient while the nurse monitored 24 simulated field casualties; (2) TCC concurrently monitored the garrison ICU and a remote military medical field exercise: the physician provided tele-mentoring during prolonged field care for a simulated casualty, and the nurse provided hospital ICU TCC; (3) the TCC nurse simultaneously monitored the ICU while providing reach-back support to field hospital nurses training in a simulation scenario. Results: TCC proved feasible during multiple exercises with concurrent tele-mentoring to different care environments including physician and nurse alternating operational and hospital support roles, and an ICU nurse managing both simultaneously. ICU staff noted enhanced quality and safety of bedside care. Field exercise participants indicated TCC expanded multipatient monitoring during mass casualties and enhanced novice caregiver procedural capability and scope of patient complexity. Conclusions: Tele-critical care can extend critical care services to anywhere at any time in support of garrison medicine, operational medicine, and mass casualty settings. An interoperable, flexibly staffed, and rapidly expandable TCC network must be further developed given the potential for large casualty volumes to overwhelm a single TCC provider with multiple duties. Lessons learned from development of this capability should have applicability for managing military and civilian mass casualty events.